A Narratological Approach to Lists in Detective Fiction - Link, Sarah J. (Crime Files, 2023)
This open access book examines how the form of the list features as a tool for meaning-making in the genre of detective fiction from the nineteenth to the twenty-first century. The book analyzes how both readers and detectives rely on listing as an ordering and structuring tool, and highlights the crucial role that lists assume in the reading process. It extends the boundaries of an emerging field dedicated to the study of lists in literature and caters to a newly revived interest in form and New Formalist approaches in narratological research. The central aim of this book is to show how detective fiction makes use of lists in order to frame various conceptions of knowledge. The frames created by these lists are crucial to decoding the texts, and they can be used to demonstrate how readers can be engaged in the act of detection or manipulated into accepting certain propositions in the text.